Implementasi pendidikan multikultural melalui pembelajaran IPS di Sekolah Dasar - I Gusti Ayu Trisna Puspita Dewi; I Wayan Lasmawan; I Wayan Kertih; I Wayan Lasmawan (Universitas Negeri Malang, 2024)
The purpose of this study is to determine the implementation of multicultural education through social studies learning in elementary schools. This study uses a literature study. Data collection techniques in this study are relevant literature sources such as scientific journals, articles, books, reports related to the research topic to obtain data or information relevant to the problem being studied. The result of this study is the implementation of multicultural education through social studies learning. Where multicultural education aims to form students who can accept, appreciate, and respect the existing diversity, both ethnicities, religions, cultures, and languages. Multicultural education is important to be applied during learning in schools and is the responsibility of a teacher in helping students implement it.